Strategi Optimalisasi Pemberdayaan UMKM di Kabupaten Ponorogo - Sri Andayani; Nekky Rahmiyati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The number of MSMEs in Ponorogo Regency based on data from the Office of Cooperatives and MSMEs in JATIM Province was 207,561. The number will continue to increase in the following years, with an increase in quantity, it does not mean that Micro and Small Enterprises (MSEs) have no problems, Problems always exist including: Low productivity, caused by low quality of human resources, especially in management, organization, technology mastery, and marketing. Limited access to capital. The situation is very difficult for MSMEs to increase business capacity or develop competitive products, although the government has provided solutions through various cheap and easy credit scheme schemes, but there are still many MSMEs that are difficult to reach. With that, we conducted a research entitled